+0  
 
0
58
1
avatar

Solve\(\begin{align*} 2^{a + 3} + 3^{b + 1} &= 33 \\ 2^{2a - 1} + 3^{b + 2} &= 11 \end{align*}\)

 

How can I start?

 Jul 20, 2020
 #1
avatar+21953 
0

To start: 

 

2a + 3 + 3b + 1  =  33   --->   8·2a + 3·3b =  33   --->   3·3b  =  33 - 8·2a 

               --->    3b  =  ( 33 - 8·2a ) / 3

 

22a - 1 + 3b + 2  =  11   --->   ½·22a + 9·3b  =  11   --->   9·3b  =  11 - ½·22a 

              --->   3b  =  ( 11 - ½·22a ) / 9

 

Setting these equal to each other:  ( 33 - 8·2a ) / 3  =  ( 11 - ½·22a ) / 9

Multiply by 9:                                     3·( 33 - 8·2a )  =  ( 11 - ½·22a )

                                                                99 - 24·2a  =  11 - ½·22a 

Multiply by 2:                                         198 - 48·2a  =  22 - 22a

                                                      22a - 48·2a - 176  =  0

Factor:                                             (2a - 4)(2a - 44)  =  0

 

So, either:  2a  =  4   --->   a  =  2

            or:  2a  =  44   --->   a  =  log(44) / log(2)

 

etc ....

 Jul 20, 2020

40 Online Users

avatar